2017
DOI: 10.1136/bmjpo-2017-000092
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood RNA gene expression in children with pneumococcal meningitis: a prospective case–control study

Abstract: IntroductionInvasive pneumococcal disease (IPD), caused by Streptococcus pneumoniae, is a leading cause of pneumonia, meningitis and septicaemia worldwide, with increased morbidity and mortality in HIV-infected children.ObjectivesWe aimed to compare peripheral blood expression profiles between HIV-infected and uninfected children with pneumococcal meningitis and controls, and between survivors and non-survivors, in order to provide insight into the host inflammatory response leading to poorer outcomes.Design a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Annexin 3 is found in myeloid cells in specific granules that are translocated upon cell activation (68) and interactions between the annexin family proteins and S100A proteins have previously been described (69). ANXA3 is also upregulated together with S100A9 and S100A12 in peripheral blood in children with severe infections (70). These findings suggest that interactions between annexin 3 and S100A alarmins in relation to monocyte function and immune activation warrant further investigation.…”
Section: Discussionmentioning
confidence: 78%
“…Annexin 3 is found in myeloid cells in specific granules that are translocated upon cell activation (68) and interactions between the annexin family proteins and S100A proteins have previously been described (69). ANXA3 is also upregulated together with S100A9 and S100A12 in peripheral blood in children with severe infections (70). These findings suggest that interactions between annexin 3 and S100A alarmins in relation to monocyte function and immune activation warrant further investigation.…”
Section: Discussionmentioning
confidence: 78%
“…inflammation, immunity, blood): several recent publications have reported an increased abundance of ANXA3 transcripts in the blood of patients with colorectal cancer, pancreatic cancer, 29,30 Huntington's disease, cluster headaches, psoriasis and pneumococcal meningitis. [31][32][33][34] In the latter study, the context of which is most relevant to the topic of this review, ANXA3 was 1 of 11 markers found to be differentially expressed in the blood of children with meningitis compared with uninfected controls (the initial discovery was made in 12 subjects, and then validated using a targeted polymerase chain reaction panel in a set of 229 subjects). 31 Relatively few studies have examined a functional role for ANXA3 in immunity and inflammation.…”
Section: Additional Reference Datasets Inform On Anxa3 Restriction Anmentioning
confidence: 99%
“…It consists of a multitude of primer pairs and fluorescence-labelled probes, preloaded and dried onto a surface, that bind with high specificity to complementary sequences of nucleic acid [7]. While microarrays have been used extensively in the fields of cancer research and clinical genetics [8–13], more recently they have drawn growing attention for their potential application to infectious diseases [14–19]. While several studies have explored the comparative sensitivity and specificity of diagnostic microarrays in identifying a broad range of pathogens [20–32], the value and implications of their introduction to clinical practice remain undetermined.…”
Section: Introductionmentioning
confidence: 99%